Effect of blower rotational frequency on performance of blower in an air-assist tractor mounted sleeve boom sprayer - SHAHARE, P U; MATHUR, S M (The Indian Journal of Agricultural Sciences, 2011)
The efforts have been made to design and develop axial flow blower for sleeve boom sprayer during 2001-2003 at ASPEE Research and Development Foundation, Mumbai, which could be operated by most common size tractor in India. The performance of prototype sprayer different blower rotational speeds was studied in laboratory as well as in the field. The laboratory test data revealed that the air discharge, air velocity and air pressure of blower had a linear relationship with the blower rotational frequency. However the power consumption and efficiency had a quadratic relationship with the blower rotational frequency. These performance parameters met the requirement of cotton crop and found within the limit of the available power of most comnlon size tractor in the country. In field test its performance was also found satisfactory.